Ethnobotanical aspects of some geophytes from Ergan Mountain, Turkey - Korkmaz, Mustafa; Alpaslan, Zennettin; Turgut, Nevzat; Ilhan, Veli (Bangladesh Journal of Botany, 2015)
The genotypes of Ergan mountain, Erzican, Turkey were studied and documented. A total of 25 taxa belonging to 14 genera and 9 families have been collected in this study. Local name, used plant parts and the ethnobotanical uses of the geophyte - species were determined. Of the recorded taxa, 48% belonged to Irano- Twianian phytogeographic region, 12% to Europe-Siberian region and 4% to Mediterranean region. Five taxa namely, Allium armenum Boiss. & Kotschy, A. sintenisii Freyn, Muscentoiceleste Formin, Fritillaria pinardii Boiss. and Tulipa armena sbusp. Lyia (Baker) Marais recorded from the study area are endemic to Turkey. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21604 Bangladesh J. Bot. 43(3): 315-321, 2014 (December)